2017
DOI: 10.1002/hup.2577
|View full text |Cite
|
Sign up to set email alerts
|

New psychoactive substances: Purchasing and supply patterns in Australia

Abstract: NBOMe consumers and those who nominated online markets as their main NPS source reported greater engagement with for-profit supply; it is unclear if these individuals have "drifted" into dealing or if they were already engaged in such activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…Compared to other surveys on the issue (European Commission 2014; Gunderson et al 2014;Burns et al 2014;Sutherland et al 2017), we found relatively high rates of NPS users buying directly from online suppliers, with almost one third of respondents. Although it is not surprising that this applies more to the online users in our survey, there are sizeable proportions of respondents in the two other groups who purchase NPS on the Internet as well, including 12% of marginalized users.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Compared to other surveys on the issue (European Commission 2014; Gunderson et al 2014;Burns et al 2014;Sutherland et al 2017), we found relatively high rates of NPS users buying directly from online suppliers, with almost one third of respondents. Although it is not surprising that this applies more to the online users in our survey, there are sizeable proportions of respondents in the two other groups who purchase NPS on the Internet as well, including 12% of marginalized users.…”
Section: Discussioncontrasting
confidence: 89%
“…For example, in a German survey directed to NPS-experienced persons (unpublished data from survey presented in Werse and Morgenstern 2015), the majority (71%) of past-30-days users of herbal blends with synthetic cannabinoids stated that they bought these drugs from the Internet (vs. 28% from friends and 15% from a shop; the latter being officially banned in Germany at that time 1 ). Conversely, in an Australian survey, among the past 12-month-NPS (mainly psychedelics) users (Sutherland et al 2017), the majority (62%) nominated friends or acquaintances as the main source (vs. 17% dealers and 9%, respectively, shops or online vendors). The latter study also found a high proportion of users who supply these drugs among their own friends.…”
mentioning
confidence: 88%
“…By this definition, they are first and foremost tweaked molecules seeking to simultaneously evade detection and/or classification and produce a pleasurable and profitable high. But Sutherland et al (2017) draw attention to “older-new” drugs such as DMT (dimenthyltryptamine), synthesized long ago but only recently popularized, and ask whether these should be included. Others wonder whether natural-occurring substances such as Hawaiian baby woodrose, long used in indigenous communities but only recently popular in the West, should have their place alongside their synthesized brethren (Favretto, Pascali, & Tagliaro, 2013; Tittarelli, Mannocchi, Pantano, & Romolo, 2015).…”
Section: Multiplicity Versus Singularitymentioning
confidence: 99%
“…Search engines have recorded an increased trend in online interest into the purchasing of and information seeking around phenybut (Li & Sundararajan, 2015). In the past two years, public health concerns have been raised around this potentially harmful dietary supplement in a number of EU Member States (France, Sweden), the US and Australia (Schifano, 2015;Wong et al, 2015;Li & Sundararajan, 2015;Owen et al, 2016;Merchan et al 2016;Sutherland et al, 2017;Barnard et al, 2017). This Short Communication provides a comprehensive narrative review of extant literature currently available on this GABA derivative.…”
Section: Novel Psychoactive Substancesmentioning
confidence: 99%